Bottom-up, scalable synthesis of anatase nanofilament-based two-dimensional titanium carbo-oxide flakes. (April 2022) - Badr, Hussein O.; El-Melegy, Tarek; Carey, Michael; Natu, Varun; Hassig, Mary Q.; Johnson, Craig; Qian, Qian; Li, Christopher Y.; Kushnir, Kateryna; Colin-Ulloa, Erika; Titova, Lyubov V.; Martin, Julia L.; et al.
Graphical abstract: Abstract: Two-dimensional (2D) materials offer advantages that their 3D counterparts do not. The conventional method for the bulk synthesis of 2D materials has predominantly been through etching layered solids. Herein, we convert – through a bottom-up approach – 10 binary and ternary titanium carbides, nitrides, borides, phosphides, and silicides into 2D flakes by immersing them in a tetramethylammonium hydroxide solution at temperatures in the 25–85 °C range. Based on X-ray diffraction, density functional theory, X-ray photoelectron, electron energy loss, Raman, X-ray absorption near edge structure spectroscopies, transmission and scanning electron microscope images and selected area diffraction, we conclude that the resulting flakes are carbon containing anatase-based layers that are, in turn, comprised of ≈ 6 × 10 Å 2 nanofilaments in cross-section some of which are few microns long. Electrodes made from some of these films performed well in lithium-ion and lithium-sulphur systems. These materials also reduce the viability of cancer cells thus showing potential in biomedical applications. Synthesizing 2D materials, at near ambient conditions, with non-layered, inexpensive, green precursors (e.g., TiC) is paradigm shifting and will undoubtedly open new and exciting avenues of research and applications.